Single Crystal Proton Conduction Study of a Metal Organic Framework of Modest Water Stability - Joarder, Biplab; Lin, Jian-Bin; Romero, Zaida; Shimizu, George K. H (Journal of the American Chemical Society, 2017)
A sulfonated indium (In) metal organic framework (MOF) is reported with an anionic layered structure incorporating hydrogen-bonded dimethylammonium cations and water molecules. The MOF becomes amorphous in >60% relative humidity; however, impedance analysis of pelletized powders revealed a proton conduction value of over 10–3 S cm–1 at 25 °C and 40% RH, a very high proton conduction value for low humidity and moderate temperature. Given the modest humidity stability of the MOF, triaxial impedance analyses on a single crystal was performed and confirmed bulk proton conductivity over 10–3 S cm–1 along two axes corroborating the data from the pellet.